AN ANALYSIS OF DIRECTIVE SPEECH ACTS IN THE FAULT IN OUR STARS MOVIE SCRIPT - Feby Rosella Wijaya; Jauhar Helmie (Universitas Suryakancana, 2019)
Pragmatics is branch of linguistics studies that attracts the writer to learn more about it. This study aims to identify the directive speech acts performed in “The Fault in Our Stars” movie script. Moreover, this study investigated how often the direct speech acts performed and which type of directive speech acts that are most frequently used in the movie script. The writer uses qualitative research method by collecting data from read the movie script, analyzing the dialogues of each characters, watch the movie and read the library research. A total of 40 directive speech acts were successfully identified. The result of analysis shows that the illocutionary acts with directive speech acts of suggest is the most frequently in the movie script (3, 50%). The least frequently used locutionary with the directive speech acts of order in the movie script (0, 0%). This study is expected to give some useful insights in understanding what directive speech acts is. The writer hopes people can not only produce speech acts in their daily activities, but also understand why and how people react or response directive speech acts. Keywords: Directive speech acts, movie script, dialogues, qualitative.